Reaksi Sinyal Keuangan Terhadap Harga Saham Sektor Pertanian di Indonesia - Faizal Ridwan Zamzany; Edi Setiawan; Elmy Nur Azizah (Esensi: Jurnal Bisnis dan Manajemen, 2018)
Financial reaction signal is one of the crucial points to predict the stock’s price. This study aims to identify the financial reaction signal toward the stock’s price on the agricultural sector in Indonesia. The variables studied were Return on Equity (ROE), Debt to Equity Ratio (DER), Market Value Added (MVA) as independent variables and Stock Price as the dependent variable. Using purposive sampling, the sample of this study to be 11 companies agricultural sector is listed on IDX (2012-2016). The method of this research is the regression analysis of panel data. The result shows that ROE and DER have no significant effect on the stock price in the agricultural sector. While the results shows MVA have a significant influence on the stock price in the agricultural sector.DOI: 10.15408/ess.v8i2.7598